2017
DOI: 10.1002/ajmg.a.38280
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and maladaptive functioning in Kleefstra syndrome compared to other rare genetic disorders with intellectual disabilities

Abstract: Detailed neurobehavioural profiles are of major value for specific clinical management, but have remained underexposed in the population with intellectual disabilities (ID). This was traditionally classified based on IQ level only. Rapid advances in genetics enable etiology based stratification in the majority of patients, which reduces clinical heterogeneity. This paper illustrates that specific profiles can be obtained for rare syndromes with ID. Our main aim was to study (mal)adaptive functioning in Kleefst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…Our epigenetic analysis disclosed the potential molecular mechanisms impaired in the Kleefstra syndrome. Interestingly Tdo2 , an enzyme indirectly involved in serotonin metabolism ( 46 ), is in our data up-regulated only in Ehmt1 +/− (2.2-fold H3K4me3, 1.7 RNA-seq plus changes in H3K4me1, H3K27ac, H3K36me3, DNA methylation), suggesting that serotonin deregulation could be one underlying cause of the depressive/mood disorders we observed in patients with Kleefstra syndrome ( 47 ). Also the Protocadherins ( Pcdhs ), cell-adhesion molecules that confer unique identities to individual neurons ( 30 , 31 ), appeared extensively repressed specifically in Ehmt1 +/− brain.…”
Section: Discussionmentioning
confidence: 49%
“…Our epigenetic analysis disclosed the potential molecular mechanisms impaired in the Kleefstra syndrome. Interestingly Tdo2 , an enzyme indirectly involved in serotonin metabolism ( 46 ), is in our data up-regulated only in Ehmt1 +/− (2.2-fold H3K4me3, 1.7 RNA-seq plus changes in H3K4me1, H3K27ac, H3K36me3, DNA methylation), suggesting that serotonin deregulation could be one underlying cause of the depressive/mood disorders we observed in patients with Kleefstra syndrome ( 47 ). Also the Protocadherins ( Pcdhs ), cell-adhesion molecules that confer unique identities to individual neurons ( 30 , 31 ), appeared extensively repressed specifically in Ehmt1 +/− brain.…”
Section: Discussionmentioning
confidence: 49%
“…Kleefstra syndrome is caused by deletions or mutations of the EHMT1 gene, encoding a histone methyltransferase, and, like PMS, presents with ID, ASD, severe speech deficits, and hypotonia, in addition to distinctive facial features. At least six individuals with Kleefstra syndrome have been reported with severe behavioral regression developing during adolescence or adulthood, with periods of apathy and catatonia-like behaviors [6264]. Individuals with Kleefstra syndrome also exhibit a high prevalence of depression, psychosis, and obsessive–compulsive disorder, with a general decline in functioning in all patients older than 18 years, usually preceded by severe sleep problems [65].…”
Section: Discussionmentioning
confidence: 99%
“…Another disorder for which Drosophila contributed much of our current knowledge is Kleefstra syndrome. The disorder, caused by haploinsufficiency of the eukaryotic histone methyltransferase 1 gene ( EHMT1 ) (Kleefstra et al, 2010; Vermeulen et al, 2017), is characterized by ID, comorbid ASD in all patients reported so far (Vermeulen et al, 2017), behavioral problems and other clinical features, including recurrent infections and obesity (Kleefstra et al, 2012). Loss of Drosophila G9a , the ortholog of EHMT1 , only resulted in subtle anomalies of da neurons and did not show other detectable nervous system architecture anomalies (Kramer et al, 2011).…”
Section: From Fundamental Gene Function Insights Towards Molecular Nementioning
confidence: 99%